RELATIONSHIP BETWEEN SOCIOCULTURAL FACTORS AND SYMPTOMS OF MENOPAUSE: MEANINGS ATTRIBUTED BY WOMEN ASSISTED AT A BASIC HEALTH UNIT (Fiep Bulletin - online, 2012)
From the observation that distinct groups of women experience menopause differently, much has been discussed about the influence of demographic, cultural and social aspects in determining the symptoms of this phase. From this, this study sought to characterize meaningful issues on the symptoms of menopause and its relationship with the socio-cultural reality of women attended in a Basic Health Unit for the Family. It is a descriptive and exploratory study with qualitative approach. The participants in the study were 14 women with age that corresponds to climacteric process period. Data were collected through semi-structured interviews and analyzed by the use of Spink idea association method. It was noticed that most women did not have enough knowledge on this particular period, confusing it with menopause itself, as was also seen that there is a relationship between socio-cultural factors and symptoms felt. Therefore, the development of practices of health education by health professionals to provide information to the population is necessary in order to provide a holistic health care practice, considering the patient as a bio-psychosocial one.
Keywords: Menopause; Symptoms; Socio-cultural factors